Nanobody‐mediated complement activation to kill HIV‐infected cells - Maria Lange Pedersen; Dennis Vestergaard Pedersen; Mikael Becher Lykkegaard Winkler; Heidi Gytz Olesen; Ole Schmeltz Søgaard; Lars Østergaard; Nick Stub Laursen; Anna Halling Folkmar Rahimic; Martin Tolstrup (EMBO Molecular Medicine)
Abstract The complement system which is part of the innate immune response against invading pathogens represents a powerful mechanism for killing of infected cells. Utilizing direct complement recruitment for complement‐mediated elimination of HIV‐1‐infected cells is underexplored. We developed a novel therapeutic modality to direct complement activity to the surface of HIV‐1‐infected cells. This bispecific complement engager (BiCE) is comprised of a nanobody recruiting the complement‐initiating protein C1q, and single‐chain variable fragments of broadly neutralizing antibodies (bNAbs) targeting the HIV‐1 envelope (Env) protein. Here, we show that two anti‐HIV BiCEs targeting the V3 loop and the CD4 binding site, respectively, increase C3 deposition and mediate complement‐dependent cytotoxicity (CDC) of HIV‐1 Env‐expressing Raji cells. Furthermore, anti‐HIV BiCEs trigger complement activation on primary CD4 T cells infected with laboratory‐adapted HIV‐1 strain and facilitates elimination of HIV‐1‐infected cells over time. In summary, we present a novel approach to direct complement deposition to the surface of HIV‐1‐infected cells leading to complement‐mediated killing of these cells.